Anachronism at Work: Villains and Enemies as Turks in Early Modern Religious Art in Genoa and Liguria - Stagno, Laura; Borniotto, Valentina (IKON, 2022)
Abstract In western Early Modern imaginaire, the Ottoman enemy was often perceived, at a symbolic level, as the quintessence of threat and persecution against the Catholic faith. Figures of ‘Turks’, identified by way of easily recognizable attributes (such as the turban), were therefore substituted for other, radically different characters in a plurality of visual narratives. In a semantically significant anachronism, Turks populated Old and New Testament scenes as well as the depictions of the martyrdoms of Christians persecuted by the Romans in the first centuries. In parallel, the same attributes were also sometimes superimposed on the figures of other, contemporary enemies of the faith, who lacked an established iconographic tradition of their own: namely the Protestant ‘heretics’. This paper aims to illustrate this visual device through a selection of significant case studies taken from the territory of the Republic of Genoa, a state characterized by a long-standing involvement in the fight against Ottoman forces and Barbary corsairs. Abstract Anakronizam na djelu: zlikovci i neprijatelji prikazani kao Turci u ranonovovjekovnoj religijskoj umjetnosti Genove i Ligurije U ranonovovjekovnom imaginariju Zapada, osmanski se neprijatelj na simboličkoj razini često doživljavao kao kvintesencija prijetnje i progona katoličke vjere. Prikazi „Turaka”, identificirani prema lako prepoznatljivim atributima kao što je turban, postaju zamjena za Druge, radikalno različite likove u mnoštvu vizualnih narativa. U semantički značajnom anakronizmu, Turci su nastanili starozavjetne i novozavjetne scene kao i prikaze mučeništava kršćana koje su progonili Rimljani u prvim stoljećima. Isti se atributi ponekad koriste za prikaze drugih suvremenih neprijatelja vjere, kojima je nedostajala vlastita ikonografska tradicija - protestantskih „heretika”. Ovaj rad ima za cilj ilustrirati ovaj vizualni instrumentarij kroz izbor nekoliko studija slučaja preuzetih s područja Republike Genove, države koju karakterizira dugotrajno sudjelovanje u borbi protiv osmanskih snaga i barbarskih gusara.